TEORI INSTITUSIONAL DALAM PENYUSUNAN DAN PUBLIKASI LAPORAN TAHUNAN SEKTOR PUBLIK (STUDI KASUS PADA KEMENTERIAN DAN LEMBAGA NEGARA DI INDONESIA) - Joko Kisworo; Elvia Rosantina Shauki (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2019)
The annual report, which is internationally recognized as an important tool for accountability and for delivering good information, has only been prepared by a few Ministries / State Institutions (MS/I) in Indonesia. This results in a lack of transparency and a lack of community participation. This study uses an institutional theory approach and aims to analyze the differences in MS/I motivation in the preparation and publication of annual reports and formulate efforts to increase that motivation. This research is a case study research by exploring the phenomena that occur in the preparation of MS/I annual reports and institutional factors that become the background. Data collection was carried out by distributing open-ended question questionnaires to Data and Information Management Officers from 86 MS/I. Respondents' answers were analyzed using content analysis techniques, thematic analysis, and constant comparative analysis. The results showed that the dominant logic is symbolic carriers at the national level, that is the logic that the preparation of annual reports is an "obligation" to implement the Act. Material carriers affect only the routines factor while relational systems and artifacts are not found to be constrained. Normative isomorphism occurs in all MS/I that are respondents of the study, while coercive isomorphism and mimetic isomorphism occur in 60% of MS/I. To encourage motivation for the preparation of annual reports, the government must prepare a clear regulation, standardized guidelines, internal SOPs and implement annual report awards.